Dinamika Kelompok Tani di Desa Belanting Kecamatan Sambelia Kabupaten Lombok Timur - IZZA, QOMARATUL; PITANA, I GDE; PARINING, NYOMAN (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Dynamics Of Farmer Group in Belanting Village, Sambelia District, East Lombok Regency. Farmer group dynamics cover all activities which include initiative, creative power, and concrete actions taken by administrators and members of farmer groups in implementing agreed group work plan. This research aims to analyze the dynamics of farmer groups in Belanting Village, Sambelia District, East Lombok Regency. Locations were selected by purposive sampling. The number of samples is 100 respondents who taken with a probability sampling technique that is proportionate random sampling with using Slovin's. Data collection is sourced from primary data and secondary data using interviews and documentation. Variables were measured by ordinal scale and interval scale which were analyzed by quantitative descriptive analysis. The results showed that the dynamics of all farmer groups in the village of Belanting is categorized as dynamic with the highest score from the Mele Pacu Farmer Group and a score of The lowest is the Tekad Sejahtera Farmer Group with a total percentage value of 96.30%. This dynamic demonstrated by strong interaction and cooperation to achieve group goals. Group dynamics must be maintained and are expected to increase responsibility administrators and group members.